2022
DOI: 10.1186/s12903-022-02165-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple idiopathic external cervical root resorption in patient treated continuously with denosumab: a case report

Abstract: Background External root resorption is an irreversible loss of dental hard tissue as a result of odontoclastic action. Multiple external cervical root resorptions in permanent teeth are rare. The exact cause of external cervical root resorption is unclear. It is currently well established that RANK/RANKL signaling is essential for osteoclastogenesis and osteoclast-mediated bone resorption. Denosumab is an anti-RANKL antibody used for the treatment of postmenopausal osteoporosis. RANK/RANKL path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…An osteoporosis patient developed MICRR after denosumab discontinuation, and the author believed that this may be a potential cause of MICRR (Deeb et al, 2019). Meanwhile, in two recent case reports, patients developed MICRR despite continued denosumab treatment for osteoporosis or de novo metabolic breast cancer metastasized to bone (Beaumont et al, 2022; Mikušková et al, 2022). Only one study reported a family cluster of MICRR cases and reported that three of the four affected family members had missense mutations in the IRF8 gene heterozygous c.1219 G>A. Functional studies have suggested that this mutation may inhibit IRF8 expression and weaken IRF8 protein function to promote osteoclasts generation at the transcription level and increase the risk for root resorption (Thumbigere‐Math et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An osteoporosis patient developed MICRR after denosumab discontinuation, and the author believed that this may be a potential cause of MICRR (Deeb et al, 2019). Meanwhile, in two recent case reports, patients developed MICRR despite continued denosumab treatment for osteoporosis or de novo metabolic breast cancer metastasized to bone (Beaumont et al, 2022; Mikušková et al, 2022). Only one study reported a family cluster of MICRR cases and reported that three of the four affected family members had missense mutations in the IRF8 gene heterozygous c.1219 G>A. Functional studies have suggested that this mutation may inhibit IRF8 expression and weaken IRF8 protein function to promote osteoclasts generation at the transcription level and increase the risk for root resorption (Thumbigere‐Math et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Deeb et al (2019) reported that one patient developed MICRR after denosumab discontinuation and proposed the "rebound effect hypothesis." Meanwhile, subsequent studies reported two MICRR patients during denosumab use, which overturned this hypothesis (Beaumont et al, 2022;Mikušková et al, 2022). Denosumab, a human monoclonal RANKL-directed antibody, prevents RANK receptor binding, thereby decreasing osteoclast-induced bone resorption (Miller, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECR is mainly asymptomatic and would incidentally be detected through radiographic examinations unless it involves the pulp or periodontal tissues. Since effective treatments for ECR are needed to be timely, precise identification of their location and magnitude is crucial 4 , 8 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Although classification using 2D methods can be problematic, particularly for molars, they still play an important role in the preliminary treatment planning for ECR. Recently, cases of ECR with different aetiologies, including medications have been reported [ 4 , 5 ]. In addition, histopathological, cone-beam computed tomography (CBCT), micro-CT, nano-CT, and scanning electron microscopy have revealed different pathogenesis mechanisms [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%